(untitled) (Revista de Ensino em Artes, Moda e Design, 2025)
This article investigates the costume design process in comic books through a comparative analysis between human-made and artificial intelligence (AI)-generated creations, focusing on the character Wonder Woman. The research combines a bibliographic review and aesthetic analysis to examine the formal and conceptual differences between costumes designed by artists and those produced by AI systems from textual prompts. The study discusses the potential and limitations of generative AI tools in the field of costume design, particularly regarding creativity, visual coherence, and fidelity to the original narrative universe. The results show that, although AI is capable of generating sophisticated visual solutions, it still struggles to capture the interpretive and stylistic nuances that are intrinsic to human artistic creation. Thus, this work contributes to the debate on design methodologies and the role of AI in contemporary creative processes.